Meningkatkan Kepercayaan Diri Dengan Mengimplementasikan Konseling Kelompok Teknik Asertif Pada Siswa Kelas XI-2 SMK Negeri 1 Dolok Merawan - Hendra Wagner Lumban Tobing (Journal of Creative Student Research, 2024)
This research aims to increase students' self-confidence by implementing assertive technical group counseling for class XI-2 students at SMK Negeri 1 Dolok Merawan. The method used in this research is counseling guidance action research (PTBK). The subjects in this research were 10 students in class XI-2 of SMK Negeri 1 Dolok Merawan who had high, medium and low self-confidence so that group dynamics occurred within them. The research was carried out in 2 cycles consisting of 3 meetings in cycle I and 2 meetings in cycle II. The data collection techniques used were questionnaire instruments and observation sheets. The data analysis technique used is quantitative descriptive analysis and qualitative descriptive analysis. The results of the research showed that there was an increase in students' self-confidence through assertive technique group counseling, this can be seen from the results of the results of the self-confidence scores of students in class post action cycle II. This shows that assertive technical group counseling services can increase the self-confidence of class XI-2 students at SMK Negeri 1 Dolok Merawan for the 2022/2023 academic year.